(untitled) (Environment & Health, 2022)
There is performed a study of cancer incidence in the population affected by the Chornobyl accident. Analysis of demography situation has shown that unlike Western European countries with increasing life expectancy this index was notably decreased in Ukraine in 2005–2006 with slow growth during 2006–2019. Certainly this circumstance may influence on cancer incidence rate because the highest risk of malignant tumours is just in elderly age. Goal: to determine the frequency and risk of malignant neoplasms in groups of the population of Ukraine that were exposed to radiation as a result of the Chоrnobyl accident in the remote post-accident period. Materials and methods. The study was conducted on the basis of long-term monitoring of malignant tumours in the groups of victims – clean-up workers of 1986–1987, evacuees from the exclusion zone, residents of the territories most heavily contaminated with radionuclides. Results. There was a significant excess of the expected level of incidence of thyroid cancer among the participants in liquidation of the accident consequences (PLAC) - 4.5 times, evacuees - 3.8 times, residents of territories contaminated with radionuclides - 1.3 times. Leukaemia and lymphoma incidence rate in residents of contaminated territories increased sharply in the first years after the accident but decreased in the next years and not exceeded the level if Kyiv and Zhytomyr regions and Ukraine at whole. In a joint Ukrainian-American analytical epidemiological case-control study dose dependent excess relative risk of leukaemia (ERR/Gy) was proved in clean-up workers and defined at level 2.38 (0.49–5.87) in 1986–2006. A significant excess of the national level of incidence of breast cancer was determined only in women - PLAC in 1986–1987. In 1994–2019 SIR was 156.3% (95% CI: 141.0–171.5). Conclusions. Because latency period for different forms of radiation related malignancies might be very long further special attention should be paid not only to nosological forms mentioned above but also to cancers of the other sites.